Assessing intra-annual growth dynamics in climatically contrasting years, sites, and tree species using dendrometers and wood anatomical data - Annette Debel; Zeynab Foroozan; Martin Häusser; Stephan Raspe; Achim Bräuning (Frontiers in Forests and Global Change, 2024)
Detecting the intra-annual dynamics and courses of secondary tree growth enables the accurate identification of crucial steps in the forming of a new tree ring. Furthermore, comparing the high-resolution recordings of tree growth with environmental conditions allows assessment of the influence of weather on wood formation processes. This study investigates the intra-annual growth performance of conifer species and European beech at two high- and two low-elevation sites in Bavaria, southeast Germany. We measured stem circumference changes with electronic band dendrometers and cambial dynamics by collecting microcores at biweekly intervals. We analyzed growth variations between the consecutive years 2020 and 2021, which showed distinct climatic differences during the growing seasons. While warm and dry conditions prevailed in spring and summer in 2020, spring in 2021 was comparatively cold, and summer precipitation was high. Different tree growth patterns were observed in the contrasting years 2020 and 2021. Distinct growth reductions occurred in the drier year 2020 for most of the studied tree species, while trees showed wider tree rings in 2021 despite of low growth rates at the beginning of the growing season. Climate-growth correlations exposed the intraseasonal influence of climatic conditions, particularly available soil water, water vapor pressure deficit, and soil temperature, on short-term tree responses. Wood anatomical analysis and daily stem diameter variations proved to be valid monitoring methods to assess individual wood formation processes and to identify species-specific tree responses to the influence of climatic conditions. However, combining both methods represents the most reliable approach due to the mutual ability to compensate for each other’s deficiencies. While dendrometers provided a very accurate and high-resolution record of intra-annual tree growth, wood anatomical analyses were more reliable in determining the exact onset and cessation of wood formation. For this reason, combining both is recommended for assessing prospective tree growth performance in the context of climate change.